2010
DOI: 10.1111/j.1756-185x.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Behcet’s disease in Iran: analysis of 6500 cases

Abstract: Behcet's disease is mainly seen in young people. The most frequent symptoms are mucocutaneous, ocular and joint manifestations. Comparison with large series did not show major differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
4
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 20 publications
7
103
4
10
Order By: Relevance
“…Of 6500 Iranian patients with BD, 1.1% had vena cava thrombosis. 58 The rate of venous involvement varies between 4% and 38%. 59 Certain combinations of symptoms occur more frequently than others in patients with BD.…”
Section: Behçet's Diseasementioning
confidence: 99%
“…Of 6500 Iranian patients with BD, 1.1% had vena cava thrombosis. 58 The rate of venous involvement varies between 4% and 38%. 59 Certain combinations of symptoms occur more frequently than others in patients with BD.…”
Section: Behçet's Diseasementioning
confidence: 99%
“…Davatchi had summarized 6500 cases in Iran, the frequency of aneurysm was 0.5%. 1) Saadoun showed that the main cause of death in BD patients was major vessel disease, mainly arterial aneurysm and Budd-Chiari syndrome, about 43.9% 4) Medicine and surgery therapy would be better to controlling the symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of vascular involvement is about 8%, 1) among which aneurysm is rare. We described a male with a five years history of BD, who developed an ascending aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Japan, the mean age of onset was found 36.8 [24]. The mean age of onset of BD in many countries was shown in Table 2 [5,13,15,[23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Age and Gendermentioning
confidence: 99%